Metformin Improves the Senescence of Renal Tubular Epithelial Cells in a High-Glucose State Through E2F1 - Liang, Dan; Li, Zhiyang; Feng, Zhaowei; Yuan, Zhiping; Dai, Yunli; Wu, Xin; Zhang, Fan; Wang, Yuanyuan; Zhou, Yuxia; Liu, Lingling; Shi, Mingjun; Xiao, Ying; et al. (Frontiers in Pharmacology, 2022)
Diabetic kidney disease is a major cause of chronic kidney condition and the most common complication of diabetes. The cellular senescence participates in the process of diabetic kidney disease, but the specific mechanism is not yet clear. Cell cycle-related protein E2F transcription factor 1 (E2F1) is a member of the E2F transcription factor family, it plays a key role in cellular damage under HG conditions. In this study, we explored whether metformin improves a high-glucose-induced senescence and fibrosis of renal tubular epithelial cells through cell cycle-related protein E2F1. In the in vivo experiments, the recombinant adeno-associated virus (AAV-shE2F1) knockdown E2F1 gene was injected into the tail vein of 16-weeks-old db/db mice for 8 weeks. The 16-week-old db/db mice were administered metformin (260 mg/kg/d) continuously for 8 weeks. The normal control group (NC) and diabetic model group (DM) were set up simultaneously. Mice renal tubular epithelial cells (mRTECs) were cultured in vitro. The cells were randomly divided into the following groups: normal glucose (NG, containing 5.5 mmol/L glucose), high glucose group (HG, containing 30 mmol/L glucose), NG/HG metformin intervention group (NG/HG + Met), NG/HG negative control siRNA transfection group (NG/HG + Control), NG/HG E2F1 siRNA transfection group (NG/HG + siRNA E2F1), HG metformin intervention and overexpression E2F1 plasmid transfection group (HG + Met + overexpress-E2F1). The expression of related indexes were detected by Western blot, real-time polymerase chain reaction (PCR), immunohistochemistry, and immunofluorescence. The results showed that E2F1 knockdown or metformin reduces the degree of renal fibrosis, DNA damage, and cellular senescence in the DM group; metformin also reduced the expression of E2F1. If E2F1 was overexpressed, the effects of metformin in delaying fibrosis and reducing DNA damage and cellular senescence could be weakened. Thus, metformin alleviates high-glucose-induced senescence and fibrosis of renal tubular epithelial cells by downregulating the expression of E2F1.